2016
DOI: 10.3389/fnhum.2016.00242
|View full text |Cite
|
Sign up to set email alerts
|

Music Performance As an Experimental Approach to Hyperscanning Studies

Abstract: Humans are fundamentally social and tend to create emergent organizations when interacting with each other; from dyads to families, small groups, large groups, societies, and civilizations. The study of the neuronal substrate of human social behavior is currently gaining momentum in the young field of social neuroscience. Hyperscanning is a neuroimaging technique by which we can study two or more brains simultaneously while participants interact with each other. The aim of this article is to discuss several fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 126 publications
(177 reference statements)
0
49
0
Order By: Relevance
“…In addition, findings from different hyperscanning studies have confirmed the robustness of alphaband implication (49,75,76). While most hyperscanning studies focus on the alpha-mu band, several studies reported interbrain coupling in the beta band (77)(78)(79); therefore, this band was analyzed as well. We hypothesized that coupling in the alpha-mu and beta bands in a pain-related interpartner network would increase during touch, compared with either the pain without touch condition or the conditions without pain.…”
Section: Significancementioning
confidence: 89%
“…In addition, findings from different hyperscanning studies have confirmed the robustness of alphaband implication (49,75,76). While most hyperscanning studies focus on the alpha-mu band, several studies reported interbrain coupling in the beta band (77)(78)(79); therefore, this band was analyzed as well. We hypothesized that coupling in the alpha-mu and beta bands in a pain-related interpartner network would increase during touch, compared with either the pain without touch condition or the conditions without pain.…”
Section: Significancementioning
confidence: 89%
“…View of the dual fMRI facility used to study mutual gaze. (B) From Acquadro et al (2016). EEG measurement of two guitar players.…”
Section: Type Of Methodsmentioning
confidence: 99%
“…Musical performances offer attractive experimental conditions since such performances combine intrapersonal action coordination and interpersonal action synchronization as well as continuous interaction. The advantages of musical settings for hyperscanning experiments are reviewed by Acquadro et al (2016). A variety of experimental paradigms allow for the investigation of different aspects of the interaction.…”
Section: Musicmentioning
confidence: 99%
“…In a balanced view, Ansari, De Smedt, and Grabner (2011) argue that 'understanding the learning process represents only one aspect of education and there are various other contextual factors that need to be considered' (114). Quite understandably, brain imaging research in music does not address the social or contextual processes, even if there are current developments that attempt to do so (Acquadro, Congedo, and De Riddeer 2016).…”
Section: Resultsmentioning
confidence: 99%